Pengaruh Substitusi Tepung Biji Rambutan Terhadap Warna dan Daya Terima Biskuit Ubi Garut - Pradipta, Raden roro Ayuning Dyah, Eni Purwani, S.Si., M.Si, Rusdin Rauf, S.TP., MP (2016)
Arrowroot biscuits is biscuit made from arrowroot flour. Rambutan seeds flour can be used as substituents of arrowroot biscuit. The impact of the rambutan seeds flour substitution will effect of colors and acceptabillity on arrowroot biscuits. The purpose of this study was to determine the effect the substitution of rambutan seeds flour on colors and acceptabillity of arrowroot biscuit. The completely randomized design was used in the research with 4 treatments substitution of tempeh flour were 0%, 5%, 10%, and 15%. Data of color, and acceptabillity of arrowrot biscuit were analyzed using one-way ANOVA and followed by Duncan at significance level of 95%. The higher value of lightness colour of arrowroot biscuits is 45,96.The higher value of redness colour is 11,12. The higher value of yellowness colour is 25,81. The higher score of colour acceptabillity is 5,27. The higher score of flavor acceptability is 5,17 The higher score of taste acceptabillity is 5,03. The higher score of texture acceptabillity is 5,43 and the higher score of overall acceptabillity is 5,27. There is an effect by the substitution of rambutan seeds flour to the colour of arrowroot biscuits. There is an effect by the substitution of rambutan seeds flour to the acceptability of arrowroot biscuits. Based on acceptabillity of arrowroot biscuit, to substitute 15% rambutan seed in arrowroot biscuits.